RELIGIOUS MODERATION: A PILLAR OF BALANCE IN MENTAL HEALTH - Zalfa Fitria Zalfa Fitria (MISBAH : Jurnal Pendidikan dan Pemikiran Islam, 2026)
Religious moderation is a key concept in maintaining social harmony within multicultural societies while also contributing to individual mental health. This study aims to analyze the role of religious moderation as a pillar of balance in life and its implications for mental health from the perspective of guidance and counseling. The method used is a literature review employing a descriptive qualitative approach. The results of the study indicate that religious moderation plays a role in reducing social conflict, mitigating the potential for radicalism, and enhancing individual psychological balance through the strengthening of resilience and stress management. Implementation in guidance and counseling is carried out through a holistic approach, multicultural education, and community support. Thus, religious moderation makes a strategic contribution to building a mentally healthy and socially harmonious society. Keywords : Religious Moderation, Mental Health, Guidance and Counseling